Γδ T cells are the predominant T cell type in opossum mammaries during lactation. (June 2019) - Fehrenkamp, Bethaney D.; Miller, Robert D.
Abstract: Milk provides mammalian neonates with nutritional support and passive immunity. This is particularly true in marsupials where young are born highly altricial and lacking many components of a fully functional adaptive immune system. Here we investigated the T cell populations in the mammaries of a lactating marsupial, the gray short-tailed opossum Monodelphis domestica . Immunohistochemistry confirmed the presence of T cells within the opossum mammaries throughout lactation. Results of quantifying transcript abundance for lymphocyte markers are consistent with γδ T cells being the most common T cell type within lactating mammaries. Numbers of γδ T cells appear to peak early during the first postnatal week, and then decline throughout lactation until weaning. In contrast, numbers of αβ T cells and γμ T cells appear to be low to non-existent in the lactating mammaries. The results support an ancient and conserved role of immune cells in the evolution and function of mammalian mammary tissue. Highlights: T cells are present in opossum mammaries throughout lactation. γδ T Cells are the predominate T cell subset in the mammaries. Abundant γδ T cells correspond to mammary development. Presence of mammary γδ T cells appears to be ancient and conserved amongst mammals.